Bridging the Digital Divide: Motivation and Academic Success in Indonesian Online Education - Satyawan, Nicole Nadya Aurelie; Utama, Firdiny Firensia (APPS Publications, 2023)
Objective – With the strict regulations put in place due to COVID-19, scholastic activities have been forced to adjust from traditional in-class learning to online learning. There are an array of benefits associated with online learning including flexibility, accessibility, independence, and stress reduction. However, many students perform substandardly in online classes and most of them prefer face-to-face learning. Interestingly, the advantages and disadvantages of online learning have been found to be influenced by student motivation. Hence, this study aims to find the relationship between motivation, online learning, satisfaction, and academic performance.Methodology – An online survey was conducted with 110 students in Indonesia and SmartPLS was used to do a quantitative analysis on the data collected. Findings – The empirical results showed that motivation significantly affects online learning, online learning significantly affects satisfaction and academic performance, and satisfaction significantly affects academic performance. Hence, this study provides several implications, especially for schools and universities to establish efficient policies and services in their online learning method. For students to be more interactive, skillful, knowledgeable and eventually perform better in their academics, motivation, online learning success, and satisfaction need to be fulfilled beforehand. Novelty – Given the unique cultural, educational, and socioeconomic factors in Indonesia, the findings may offer valuable insights into the specific challenges and opportunities of online learning in this setting.